Germany, Ireland and the Second World War in the works of Christabel Bielenberg, Francis Stuart and Hugo Hamilton - Depner, Dorothea (Trinity College (Dublin, Ireland). School of English, 2013)
Memory has become a focal point of research across several disciplines, including Irish studies. What remains unacknowledged, however, are the roots of memory's ascendancy in the worldwide engagement with the victims of the Second World War and the progression of critical discourse beyond Pierre Nora's landmark study on lieux de memoire.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin.